Theo mình nghĩ là như sau: 19/n-1 x n/9 = 19n/9(n-1)
Vì (19;9)=1 , (n;n-1)=1 =>Để 19/n-1 x n/9 = 19n/9(n-1) thuộc n :
=> 19 chia hết cho n-1 , n chia hết cho 9.
=> n-1 thuộc Ư(19) => n-1 thuộc 19; -19; 1; -1.
Ta có bảng:
n-1
19
-19
1
-1
n
20
-18
2
0
[TBODY]
[/TBODY]
(1)
n thuộc B(9)=>0; 9; -9; 18; -18; ... (2)
Từ (1) và (2) : => n thuộc -18 hoặc 0.
Thử : n = -18:
19/n-1 x n/9 = 19/-18-1 x (-18/9) = (-1) x ( -2) = 2 ( thỏa mãn )
n=0 : 19/n-1 x n/9 = 19/0-1 x 0/9 = 19/-1 x 0 = -19 x 0 = 0. ( thỏa mãn )
Vậy n = -18 hoặc n = 0.